Global oil prices and the macroeconomy: The role of tradeable manufacturing versus nontradeable services - Makram Khalil (Deutsche Bundesbank, 2020)
This paper studies the ability of manufacturing-specific shocks to explain global oil prices. In an estimated three-region DSGE model (UnitedStates, OPEC, rest-of-world) in corporating two sectors (manufacturing and services) in the oil-importing economies and featuring cross-border manufacturing supply chains, oil inventories as well as endogenous oil supply, such shocks rationalize the observed empirical pattern of a positive comovement between global oil prices and the global cyclical gap between manufacturing output and services provision. Given positive manufacturing technology shocks, oil demand and demand for intermediate manufactured goods as well as global trade decline in tandem. Of similar importance are shocks to final manufactured goods demand that are amplified by input-output linkages and international trade. From the perspective of the US, all foreign shocks that cause higher oil prices - including adverse oil supply shocks - have a positive impact on manufacturing relative to service s as well as a positive impact on aggregate core inflation and policy rates. These dynamics rationalize, to a large extent, the observed pattern during major oil price hikes, and, correspondingly (with opposite signs), during important episodes of low oil prices.
Keywords: E32; F41; Q43; 330; endogenous global oil price; trade channel; manufacturing and services; oil and the business cycle; oil intensity; intermediate inputs